Catalytic surface modification of alumina membrane for oxygen separation - Sihar, Ainun Sailah (Penerbit UTM Press, 2017)
Two types of alumina ceramic membrane in hollow fibre shape was used in this study. Both alumina hollow fibres (AHF) were sintered at different temperatures; (a) 1350oC and (b) 1450oC. In order to improve the catalytic activity of the alumina membrane for oxygen separation purposes, surface modification of the membranes was carried out using La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) perovskite catalyst. LSCF was synthesised using simple Pechini sol-gel method. The evaporation time and temperature of the LSCF-sol were varied to obtain various viscosity of catalytic sol. From XRD analysis, pure LSCF perovskite structure formed at temperature at 850oC. The morphological of unmodified and surface-modified alumina hollow fibre membranes (AHF) were studied using FESEM. The effect of LSCF catalytic sol viscosity was studied and it was found that as the viscosity of the sol increases, the amount of catalyst deposited on the alumina hollow fibre were increased. Besides, the amount of catalyst deposited on 1350 AHF was found to be higher than 1450 AHF. This result is supported by the result of pore distribution data whereby 1350 AHF was observed to be more porous than 1450 AHF, with porosity percentage of 40.38% and 28.80%, respectively. Although higher viscosity of catalytic sol could lead to a high amount of catalyst deposited on the AHF substrate, there is a tendency for micro-cracks to develop. Thus, the viscosity of the catalytic sol is important to control in order to have higher oxygen permeation flux.